A novel route for the generation of Co/CoZn/CoNi layered double hydroxides at ambient temperature. Issue 6 (24th April 2019) - Chen, Liyong; Wang, Huifang; Shen, Xiaoshuang; Zhang, Yingyue; Li, Dezhi; Duan, Chunying
Abstract : Cobalt-based LDHs with high electrocatalytic OER performance are selectively produced by simply adjusting the amount of reagents in methanol. Abstract : Although metal–organic frameworks (MOFs) can be extensively used as sacrificial templates to prepare their inorganic counterparts and vice versa, selective generation of these two types of materials in the same synthetic media is seldom involved due to the tremendous difference in composites and their thermodynamic stability. Herein, cobalt layered double hydroxides (Co-LDHs) were successfully prepared at room temperature from a typical synthetic system of zeolitic imidazolate framework-67 (ZIF-67), a methanolic solution of Co 2+ and 2-methyimidazole (Hmim). The final products from ZIF-67 to ZIF-67/Co-LDH hybrids to Co-LDHs were easily regulated while gradually increasing the concentration of Co 2+ and Hmim or the molar ratio of Co 2+ /Hmim. There was a similar variation trend in the methanol solvent used as well. The synthetic strategy even can be expanded to the selective synthesis of hetero-bimetallic CoZn-/CoNi-ZIFs and CoZn-/CoNi-LDHs.